Effects of multiaxial fatigue on typical details of orthotropic steel bridge deck. (February 2019) - Fu, Zhongqiu; Wang, Yixun; Ji, Bohai; Jiang, Fei
Abstract: Effects of multiaxial fatigue on typical details of orthotropic steel bridge deck were studied. The calculating limit of fatigue damage considering multiaxial stress was investigated. The maximum principal stress with the greatest absolute value was first proposed to judge the stress state of certain details. The fatigue details in the steel bridge deck were then classified based on structural characteristics. The influence of multiaxial fatigue on the stress state and cracking direction was also analyzed. The multiaxial fatigue deviation was introduced to determine the calculating limit which was verified by the multiaxial fatigue experiment of the deck and U-rib weld. The results show fatigue details in the steel bridge are usually in a state of multiaxial stress, and uniaxial stress is only an instantaneous state when the centerline of the wheel load coincides with that of the symmetrical details. The direction of crack growth is mainly determined by multiaxial stress and structural characteristics. If a precision of 90% is achieved, the uniaxial fatigue theory can be applied to assess the multiaxial fatigue damage when δ is smaller than 1.06413. Highlights: The maximum principal stress with the greatest absolute value was proposed to judge the stress state of fatigue details. The multiaxial fatigue deviation was introduced to determine calculating limit and verified by the fatigue experiment. The influence of multiaxial fatigue on the stress state was obtained and potential cracking direction was proposed. The function of calculating limit for multiaxial fatigue damage was fitted which can meet requirements of precisions.